miRNAs as cell fate determinants of lateral and paraxial mesoderm differentiation from embryonic stem cells - GÜLLÜOĞLU, ŞÜKRÜ (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
To date, the role of miRNAs on pluripotency and differentiation of ESCs into specific lineages has been studied extensively. However, the specific role of miRNAs during lateral and paraxial mesoderm cell fate decision is still unclear. To address this, we firstly determined miRNA profile of mouse ESCs differentiating towards lateral and paraxial lineages which were detected using Flk1 and PDGF alpha R antibodies, and of myogenic and hematopoietic differentiation potential of purified paraxial and lateral mesodermal cells within these populations. miRNAs associated with lateral and paraxial mesoderm, and their targets were identified using bioinformatics tools. The targets of the corresponding miRNAs were validated after transfection into mouse ESCs. The roles of the selected miRNAs in lateral, and paraxial mesoderm formation were assessed along with hematopoietic and myogenic differentiation capacity. Among the miRNAs, mmu-miR-126a-3p, mmu-miR-335-5p and mmu-miR-672-5p, upregulated in lateral mesoderm cells, and mmu-miR-10b-5p, mmu-miR-196a-5p and mmu-miR-615-3p, upregulated in paraxial mesoderm cells. While transient co-transfection of mmu-miR-126a-3p, mmu-miR-335-5p and mmu-miR-672-5p increased the number of lateral mesodermal cells, co-transfection of mmu-miR-10b-5p, mmumiR-196a-5p and mmu-miR-615-3p increased the number of paraxial mesodermal cells. Moreover, differentiation potential of the lateral mesodermal cells into hematopoietic cell lineage increased upon co-transfection of mmumiR-126a-3p, mmu-miR-335-5p and mmu-miR-672-5p and differentiation potential of the paraxial mesodermal cells into skeletal muscle lineage were increased upon co-transfection of mmu-miR-10b-5p, mmu-miR-196a-5p and mmu-miR-615-3p. In conclusion, we determined the miRNA profile of lateral and paraxial mesodermal cells and co-transfection of miRNAs increased differentiation potential of both lateral and paraxial mesodermal cells transiently.
Keywords: miRNA; Mouse embryonic stem cell; Mesodermal differentiation; Flk1; PDGF alpha R; HEMATOPOIETIC PROGENITOR CELLS; MUSCLE-DERIVED CELLS; IN-VITRO; ENDOTHELIAL-CELLS; SKELETAL; MICRORNAS; GENES; REGENERATION; MECHANISM; EXPRESS